De musica latine scribenda: How to approach a Latin text as a composer without summoning a demon in the process - Aliaga del Bosque, Juan Carlos (2023)
While composing vocal music, it is usually required an extra “set of rules” that is generally related with the language of the text used in the music. Each language has characteristics connected with its pronunciation, prosody, meaning, etc., that are necessary in order to set the text in a way that is understandable, but also some of these “quirks” can be exploitable and shape the music in a way that is closer to the sound, rhythm or even the culture carried by the language. This first paper on the topic addresses the use of Latin language in musical composition, as many others have tackled its pronunciation in performance but there is not much written about how a composer can use the language confidence and efficiency. In this paper, the concepts of syllable length and tonic accent in Latin will be introduced and they will be explained and applied through musical examples from different historical periods.